DISTRIBUTION OF PHISING LINKS OF MINISTRY OF EDUCATION QUOTAS ON PERSONAL INFORMATION AWARENESS - Joseph Paul John Jansz Jansz (Fox Justi : Jurnal Ilmu Hukum, 2021)
Hoax are becoming one of the things that are increasingly found in today's digital era. The types of hoaxes circulating in the community are also very diverse, one of which is the Ministry of Education and Culture quota phishing link hoax. This hoax is targeting the personal data of students, students, and people who need internet quota during this pandemic. For this reason, in this study we want to find out how aware Uninus students are about the importance of personal data security. This study uses a qualitative approach with a descriptive method, and the data collection technique is through interviews and questionnaires. This type of research data is primary data, and the research subjects are Uninus students. The object of this research is the awareness of Uninus students towards personal information, and the informants are class A students of the Communication Studies study program. As a result, the informants admitted that they had received phishing links from the Ministry of Education and Culture quota and knew that phishing links could threaten personal data and could also cause material and non-material losses. They also know the steps to avoid becoming a victim of phishing links and how to identify phishing links circulating in the community. The informants admitted that they are very aware of the importance of personal information security